Port of Matina, from Independence to the Formation of the National State (Region, Resources and Population) - Payne Iglesias, Elizeth (2021)
Here we study Matina’s economy. We consider its spatial layout, productive activities, as well as the local and regional trade. Additionally, we seek to determine what was the port’s hinterland and its area of influence, in order to assess whether it functioned as a regional core in Costa Rica’s territory, while also underscoring its role in relations with Mosquitia, Bocas del Toro and Jamaica. This paper argues that Matina and its adjacent areas maintained a population that, while small and mobile, managed to create a strategic spot through interactions with Miskitu, English and Colombian neighbors. Over time, Costa Rica’s success in cementing its control over the Caribbean slope owed a great deal to Matina.